(untitled) (Web of Scientists and Scholars: Journal of Multidisciplinary Research, 2024)
The synthesis of hydrocarbons from CO and H2 in the Fischer-Tropsch method is a complex system of chemical reactions that take place in series and in parallel with the presence of a catalyst.